Theory and Application on Cognitive Factors and Risk Management New Trends and Procedures - De Felice, Fabio; Petrillo, Antonella (IntechOpen, 2017)
Risk management is an interdisciplinary discipline that involves several aspects. It is absolutely necessary to make sure we manage risks in order to minimize their threats and maximize their potential. This book tries to investigate the complexity that characterizes risk management. It contains original research and application chapters from different perspectives and covers different areas such as human aspects, emergency management, cognitive factors, software engineering, and marketing. The idea of the book is to expand the reader's consciousness to deal with problems regarding risk management.